Rhetoric of Presidential Leadership: Critical Analysis of Indonesian Presidential Speech for Pedagogical English Public Speaking - Ferdinandus, Febryanti Abas; Prasongko, Angga; Wulandari, Sri (Jurnal Paedagogy, 2026)
This study aims to critically analyze the rhetorical strategies employed in President Prabowo Subianto’s international speeches by integrating Aristotle’s rhetorical theory with Critical Discourse Analysis (CDA) to assess their pedagogical potential as authentic models for English public speaking instruction. The research adopted a qualitative approach using a case study method. The primary data consisted of transcripts from three international speeches, which were analyzed through thematic coding. The findings indicate that the president’s speeches consistently employ logical reasoning (logos), speaker credibility (ethos), and emotional appeal (pathos) to reinforce political legitimacy and construct a positive diplomatic image. These rhetorical strategies are systematically embedded within the speech structure and reflect context-sensitive persuasive communication in international settings. The results suggest that presidential speeches can serve as valuable instructional materials for enhancing English public speaking skills, particularly in teaching structured argumentation, developing speaker credibility, and fostering cross-cultural and diplomatic communication competence.